Properties of Quasi-Oscillator in Position-Dependent Mass Formalism - S. Zare; H. Hassanabadi (Advances in High Energy Physics)
Schrödinger equation is considered within position-dependent mass formalism with a quasi-oscillator interaction term. Wave functions and energy spectra have been obtained analytically. Thermodynamic properties, information entropy, and uncertainty in coordinate and momentum spaces are calculated. To provide a better physical insight into the solutions, some figures are included.